Media Construction in the MBG Poisoning Case: An Analysis of Framing, Hegemony, and Social Learning in Kompas.com and BBC News Indonesia - Pitoyo Pitoyo; Yani Tri Wijayanti; Bella Amalia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2026)
This study analyzes media construction in the Free Nutritious Meal (MBG) poisoning case in Cipongkor District, West Bandung Regency, through framing, hegemony, and social learning in the coverage of Kompas.com and BBC News Indonesia. Using a qualitative approach, the study applies Robert N. Entman’s framing analysis, supported by Antonio Gramsci’s theory of hegemony and social learning theory. The data consist of seven news articles published in September 2025. The findings show clear differences in framing. Kompas.com presents the incident as a technical problem by emphasizing government responses and operational solutions. In contrast, BBC News Indonesia highlights the humanitarian impact and systemic weaknesses, offering a more critical perspective. The two media outlets also shape different forms of social learning: Kompas.com tends to strengthen public trust, whereas BBC News Indonesia increases concerns about the safety of the program.